Recombinant spidroins from infinite circRNA translation - Ivanov, Maksim G. (2023)
Spidroins are a diverse family of peptides and the main components of spider silk. They can be used to produce sustainable, lightweight and durable materials for a large variety of medical and engineering applications. Spiders’ territorial behaviour and cannibalism precludes farming them for silk. Recombinant protein synthesis is the most promising way of producing these peptides. However, many approaches have been unsuccessful in obtaining large titres of recombinant spidroins or ones of sufficient molecular weight. The work described here is focused on expressing high molecular weight spidroins from short circular RNA molecules. Mammalian host cells were transfected with designed circular-RNA-producing plasmid vectors. A backsplicing approach was implemented to successfully circularise RNA in a variety of mammalian cell types. This approach could not express any recombinant spidroins based on a variety of qualitative protein assays. Further experiments investigated the reasons behind this.